Molecular imaging II. - Li, K.C.P.
This paper provides an overview of the field of molecular imaging by giving representative examples to illustrate the excitement and the dynamic nature of this field. On the first paper on molecular imaging, PET, SPECT, and bioluminescence imaging were focused on. In this issue, approaches that are sometimes called "physiologic imaging" or "functional imaging" are concentrated on. Combining targeted imaging and therapy to pursue a "personalized treatment" paradigm is also discussed. The techniques discussed such as magnetic resonance imaging, biomedical ultrasonics and hyperspectral imaging for in vivo optical diagnostics have much less sensitivity than PET or SPECT but these techniques can provide biologic information in vivo that are critical for both enhancing our knowledge of systems biology and also for clinical management of patients.
Keywords: PET; SPECT; Biologic information; Bioluminescence imaging; Biomedical ultrasonics; Clinical management of patients; Functional imaging; Hyperspectral imaging; In vivo optical diagnostics; Magnetic resonance imaging; Molecular imaging; Personalized treatment; Physiologic imaging; Systems biology; Targeted imaging; Therapy